The Hypo-fractionated Radiotherapy in the Management of Pigmented Villonodular Synovitis. One center experience . - سعد بسام (Latakia University Journal -Medical Sciences Series, 2023)
This article reviews our 6 years experience of radiotherapy (RT) as adjuvant treatment of histology confirmed pigmented villonodular synovitis ( PVNS) We identified 13 patients ( 5 men and 8 women ) with diffuse PVNS of the knee who were treated with postoperative RT between 2014-2021 at Radiotherapy and chemical center in Tishreen University Hospital in Lattakia , Syria. The median patient age was 35 ( range : 18 – 60 ) years. The median period for starting radiotherapy after surgery was 5.1 weeks ( range : 0.5-12 ) weeks. All patients received hypo-fractionated external-beam radiotherapy using 3-dimensional conformal techniques. The radiation dose delivered in two phases : the whole joint 25Gy ( 10 fractions of 2.5Gy ) . The median follow-up period was 2.7 ( range , 0.5 – 5 ) years. Of the 13 patients , 12 had stable disease or were free of disease , clinically or on MRI imaging of the affected joint. 1 patients had local recurrence based on MRI imaging. None had acute or long-term complications from RT. In conclusion , local radiotherapy should be considered for patients with PVNS, in cases of extensive disease with incomplete excision and / or local recurrence.